Behavior and Pro-Inflammatory Cytokine Variations Among Submissive and Dominant Mice Engaged in Aggressive Encounters: Moderation by Corticosterone Reactivity - Audet, Marie-Claude; Mangano, Emily N.; Anisman, Hymie (Frontiers in Behavioral Neuroscience, 2010)
Psychosocial stressors contribute to the pathophysiology of affective disorders and variations of cytokine functioning have been implicated in this process. The present investigation demonstrated, in mice, the impact of stressful aggressive encounters on activity levels, plasma corticosterone and cytokine concentrations, and on cytokine mRNA expression within the prefrontal cortex (PFC) and hippocampus. As glucocorticoids have been tied to cytokine variations, mice were subdivided into low or high corticosterone responders, defined in terms of circulating hormone levels 75 min post-confrontation. Interestingly, stressor-induced effects among low and high responders varied as a function of whether mice were submissive or dominant during the aggressive bout. Agonistic encounters elicited subsequent hyperactivity, particularly among low corticosterone responders and among dominant mice. Plasma levels of corticosterone and interleukin (IL)-6 concomitantly increased after aggressive encounters and varied with dominance status and with the low versus high corticosterone response. Among the low responders corticosterone and IL-6 increases were modest and only apparent among submissive mice, whereas among high responders these elevations were more pronounced and comparable in submissive and dominant mice. Aggressive episodes also increased IL-1B and IL-6 mRNA brain expression. The IL-1B rise was greater in the PFC and hippocampus of submissive mice that were low responders. Among high responders IL-1B and IL-6 increased in both groups, although in the PFC this effect was specific to dominant mice. The data are discussed in terms of their relevance to the impact of aggressive encounters on affective behaviors, and to the role that cytokines might play in this regard.